2001
DOI: 10.1046/j.0953-816x.2001.01560.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of channel mutations in heterologously expressed α7‐nicotinic acetylcholine receptors

Abstract: Nicotinic acetylcholine receptors (nAChR) composed of chick alpha7 subunits mutated to threonine at amino acid valine-251 in the putative channel-lining M2 domain were expressed heterologously in several neuron-like and non-neuronal mammalian cell lines. Expression of mutant alpha7-nAChR is toxic to neuron-like cells of the human neuroblastoma cell lines SH-SY5Y and IMR-32, but not to several other cell types. Growth in the presence of the alpha7-nAChR antagonist methyllycaconitine (MLA) protects against neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…L250T-"gain of function" mutant mice (44) and in neuron-like cells that express the mutant chick ␣7 V251T subunit (36). Additionally, it was shown that nicotine could exert a neuroprotective effect via ␣7-nAChRs and ␣4␤2-nAChRs (12,21,32).…”
Section: Discussionmentioning
confidence: 99%
“…L250T-"gain of function" mutant mice (44) and in neuron-like cells that express the mutant chick ␣7 V251T subunit (36). Additionally, it was shown that nicotine could exert a neuroprotective effect via ␣7-nAChRs and ␣4␤2-nAChRs (12,21,32).…”
Section: Discussionmentioning
confidence: 99%
“…With a type II PAM, the tonic presence of the ␣7 agonist choline could disrupt native signaling dynamics and, if the potentiation of the calcium permeable receptor currents becomes sufficiently large to disrupt calcium homeostasis, cause cell death (Orr-Urtreger et al, 2000;Lukas et al, 2001). This could be especially true in cases of trauma or stroke, when choline concentrations in the brain increase to as high as 100 M (Jope and Gu, 1991;Scremin and Jenden, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, a PAM-based strategy may also be subject to some potentially important limitations, especially if the potentiation of the calcium-permeable ␣7 receptor currents becomes so large that calcium homeostasis is disrupted, causing cell death (Orr-Urtreger et al, 2000;Lukas et al, 2001). Nonetheless, in vivo studies with ␣7 PAMs have reported no major concerns regarding toxicity (Williams et al, 2011c), which might suggest that specific factors may prevent overactivation of ␣7 receptors in the physiological context.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid desensitization has often been proposed to represent a protective mechanism, preventing excessive Ca 2+ influx into the cell that could prove cytotoxic. Evidence for such a hypothesis was provided by the observation that mutations in the second TMD, which reduce receptor desensitization, are associated with increased cell death and are lethal in an animal model (OrrUrtreger et al, 2000;Lukas et al, 2001). An interesting parallel can be drawn with the a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors, which have fast activation and desensitization comparable with those of the a7 nAChRs (Traynelis et al, 2010).…”
Section: B Functional Properties Of A7 Nicotinic Acetylcholine Recepmentioning
confidence: 99%